BIOTECHNOLOGY OF PRODIGIOSIN: RECENT DEVELOPMENTS AND TECHNOLOGICAL CHALLENGES - Wani Devita Gunardi; Margaretha; Kris Herawan Timotius (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
Background: Prodigiosin is produced by Serratia marcescens. It has several pharmacological benefits, such as anticancer, antimicrobial, and antidaibetic. However, prodigiosin production still faces problems because it cannot be produced effectively, efficiently, and cheaply. Objective: This study aimed to conduct a review that can explain the upstream and the downstream process in prodigiosin production. Methods: Articles were searched from PubMed and ScienceDirect with the keywords prodigiosin and Serratia marcescens from Juny until September 2023 including review and original article. Relevant data and information were then extracted. Results: Prodigiosin has spectrometrical characteristics, which are crucial for evaluating its production, extraction, and purification identification. Submerged or solid-state fermentation is applicable for prodigiosin production, but solid-state fermentation is better. The kind of growing substrates and the cultural condition influence it. The use of oil-based carbon sources is recommended for the high productivity of prodigiosin. In order to have a cheap, effective, and efficient production process, different experiments have been conducted. Standard extraction and purification methods can carry out the downstream process. Conclusion: Prodigiosin can be produced via submerged or solid-state fermentation. Using cheap and readily available substrate are the key to success for the upstream and downstream process. The standard extraction and purification methods are available.This findings can be used as a basis for further research regarding large-scale production of prodigiosin with the cheap, effective, and efficient methode.